On the Mohand Transform and Ordinary Differential Equations with Variable Coefficients - Attaweel, Mohamed E.; Almassry , Haneen (Al-Mukhtar Journal of Sciences, 2020)
The Mohand transform is a new integral transform introduced by Mohand M. Abdelrahim Mahgoub to facilitate the solution of differential and integral equations. In this article, a new integral transform, namely Mohand transform was applied to solve ordinary differential equations with variable coefficients by using the modified version of Laplace and Sumudu transforms.